2022
DOI: 10.1177/13634615211066698
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and Indigenous mental health in the Circumpolar North: A systematic review to inform clinical practice

Abstract: Climate change is disproportionally impacting the Circumpolar North, with particular impacts among Indigenous populations. Environmental changes are felt in many aspects of daily life of Northern communities, including both physical and mental health. Thus, health institutions from around the Arctic must meet emerging needs, while the phenomenon remains marginal to their southern counterparts. In this systematic review, we aimed to review current scientific knowledge on the mental health impacts of climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 81 publications
1
85
0
2
Order By: Relevance
“…In an earlier review conducted only three studies reported being conceived, designed, or conducted in partnership with Indigenous communities or informed by Indigenous pieces of knowledge and values. (Lebel et al, 2022 ) In our study, we found that in eleven studies there was an involvement of indigenous peoples in the climate mitigation and adaptation process.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…In an earlier review conducted only three studies reported being conceived, designed, or conducted in partnership with Indigenous communities or informed by Indigenous pieces of knowledge and values. (Lebel et al, 2022 ) In our study, we found that in eleven studies there was an involvement of indigenous peoples in the climate mitigation and adaptation process.…”
Section: Discussionsupporting
confidence: 52%
“…Impacts of climate change on mental health happen due to restricted mobility and disrupted livelihoods and are further accentuated through changes in culture and identity, food insecurity, interpersonal stress and conflicts, and housing problems. (Lebel et al, 2022 ). In the Inuit community in northern Canada which has deep cultural connections with sea ice, the changing ice and weather conditions have been reported to result in anxiety-related episodes ( ACIA 2005 , 2022 ; Prowse & Furgal, 2009 ).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to dwindling resources resulting in food insecurity, the ecological impacts brought about by climate change can have a negative effect on mental health and spirituality. This has been noted particularly in indigenous communities, where an increased prevalence of mental health disorders coincident with climate change has been attributed to the concept of ecological grief ( Middleton et al, 2020 ; Lebel et al, 2022 ). Consistent with the correlative pattern and potential mechanistic overlap between the two conditions, NAFLD prevalence in an indigenous population was far higher than the global rate (44 vs. 32%, respectively), and indigenous communities were identified as one of the groups with the steepest increases in rates of NAFLD-related mortality over the past 10 years ( Cheah et al, 2013 ; Paik et al, 2019 ; Riazi et al, 2022 ).…”
Section: Mechanistic Synergies Between Non-alcoholic Fatty Liver Dise...mentioning
confidence: 99%